Penggunaan Insektisida Rumah Tangga untuk Mencegah dan Mengendalikan Aedes aegypti di Permukiman di Provinsi Sumatera Utara - Sunaryo Sunaryo; Dyah Widiastuti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
Dengue prevention and control still depend on insecticides usage. Household insecticides were the most preferable choice to prevent and control Aedes aegypti at settlements. The purpose of this study was to analyze the usage of household insecticides to prevent and control Ae. aegypti in settlement, especially in North Sumatra Province. The research was conducted during April-November 2015. The larvae examination and interviews were conducted on 900 respondents in three districts in North Sumatra Province (Tebing Tinggi, Pematang Siantar and Deli Serdang). The results of the study showed that the house index, container index, breteau index and densty figure in three districts were revealed that the regions were at moderate and high risk of dengue transmission. Most people in three districts use household insecticide at night to prevent dengue transmission. In conclusion, the household insecticides usage by the community in North Sumatra Province is ineffective to Ae. aegypti prevent and control in settlements, because the community only use adulticide and the time of use of insecticide is not in accordance with the activities of Ae. aegypti to transmit DHF during the daytime without any larva control activity.